Diel cycles of the particulate beam attenuation under varying trophic conditions in the NW Mediterranean Sea: Observations and modeling - Gernez, P.; Antoine, David; Huot, Y. (AGU, 2010)
The effects of the diel cycle of light intensity, while often neglected, have been reported for a variety of biogeochemical and optical quantities. In particular, a diel cycle in the particle beam attenuation coefficient (cp) appears to be a near ubiquitous feature of the optical variability in the euphotic zone and has been associated primarily with the daytime accumulation and night-time removal of particles in the size range ~0.1 to 20 microns. However, generally, in situ investigation of the cp daily variability is limited to a few days. The development of instrumented moorings allows in situ measurements to be performed at high-frequency, over long periods (years) and under varying environmental conditions (trophic state, vertical distribution of the water properties, composition of the particle community). A time series of inherent and apparent optical properties (cp, chlorophyll fluorescence, downward irradiances) has been collected at an open ocean mooring (BOUSSOLE project) in the North western Mediterranean Sea (60 km offshore Nice, France). All data are simultaneously recorded every 15 minutes at 9 m depth. This database allows us to characterize the diel variability in cp, with consideration of the physical forcing and the phytoplankton population composition (as described by monthly HPLC analyses).Using this two years time-series, we studied the changes in shape, amplitude and timing in the cp diel variability under contrasted physical and trophic situations. A diel cycle is observed whatever the season, during winter mixing, development of bloom, its collapse, and summer oligotrophic situations. The relative amplitude of the cycle is about 10-20% during mixing and oligotrophy, and at least twice as large during the spring bloom. Diel cp minima generally occur around sunrise and maxima a few hours before sunset. The specific particle rate of variation (1/cp dcp/dt) generally reaches maximum before noon, suggesting that the particle growth is more important in the first half of the photoperiod. A new model is proposed to reproduce this singular morning maximum. The rate of variation of cp is modeled as a light-dependent particle growth rate, using three parameters: maximum growth rate, growth efficiency and saturation irradiance. These parameters show important and consistent diel and seasonal variability. These results highlight the importance of considering the time-dependency of these parameters to improve the accuracy of predictive models of photosynthetic and heterotrophic particle growth in the ocean.